Effect of planting management factors on canola performance in high-residue cropping systems - Showalter, Baylee M. (Kansas State University, 2017)
Winter survival of canola (Brassica napus L.) is a challenge for producers using high-residue, no-tillage, or reduced tillage systems. In addition, as hybrid cultivars have become more available in recent years, this has brought about questions regarding best management practices to aid in mitigating winter survival challenges associated with high residue production systems. Overcoming production challenges will allow producers to diversify their no-till cropping systems with an oil seed crop having strong domestic demand. This research was undertaken to identify practices that could improve performance of canola in high-residue cropping systems. Two sets of experiments were conducted at twelve sites across Kansas from 2014 to 2016 to evaluate practices that could improve stand establishment, winter survival, and yield of winter canola. The objective of the first study conducted at 10 site years was to determine the effect of residue management, seeding density, and row spacing on stand establishment, winter survival, and yield. An innovative residue management system being developed by AGCO Corp. was compared to cooperating canola producers’ no-till residue management and planting methods in wheat residue. This on-farm experiment was conducted at ten environments across Kansas. AGCO treatments were 20 or 30-in row spacing and three seeding rates for a total of six treatments. Producer treatments included their preferred row spacing, seeding rate, and residue management practices. Winter survival increased by 11% to 29% as seeding rate decreased in 20-in rows at four of the five harvested environments. At Stafford and Kingman, the lowest yielding AGCO treatment produced 3.7 to 4.2-bushel acre⁻¹ more than the respective cooperator treatments. Reduced seeding rates in the AGCO system produced yields similar to or superior than the cooperator practice in all environments. Producers have been turning to planting canola in wide rows to facilitate residue management with strip tillage or planter residue management attachments. The objective of the second study conducted at three site-years was to determine the effect of seeding rate on winter survival and yield of hybrid and open-pollinated winter canola cultivars in 30-in rows. Treatments were four genotypes and five seeding rates for a total of twenty treatments. Winter survival increased with the lowest seeding rate at one of the three environments. At two of the three environments neither genotype nor seeding rate affected yield. These results indicate that seeding rates can be reduced from those typically used by canola producers in high residue, no-till or reduced tillage systems if residue can be adequately removed from the seed row. Both hybrid and open-pollinated winter canola cultivars responded similarly to seeding rate in 30-in rows in these experiments, indicating that similar seeding rates could be used for each type of cultivar. Management practices such as, narrow row spacing, reducing seeding rates, and adequately managing residue at planting may result in small improvements to establishment, winter survival and yield.
Keywords: Winter canola; Residue management